Irrigated Agriculture in the Brazilian Semi-Arid Region : Social Impacts and Externalities - World Bank (Washington, DC, 2013)
The aim for this study was to assess the impact of irrigation activities in the Brazilian Semi-Arid (BSA) Region, and to analyze to what extent irrigated agriculture in this region has contributed to the reduction of poverty levels and regional inequalities, income growth and distribution, and the creation of quality jobs, with the aim of contributing to the establishment of guidelines for a regional development strategy. The study indicates that, overall, public investment in irrigated agriculture could be an effective strategy for boosting regional development, increasing exports and alleviating poverty in the BSA. The necessary dynamics for this are mainly: an abundant and reliable water supply, well-designed projects, competent project management, strong political support, timely financing and implementation, titled land parcels, practical urban support, adequate transport infrastructure, industrious farmers, participation of entrepreneurial producers, effective technological support, and, skilled marketing. The analysis also showed that: a) It takes about 10 to 15 years for public schemes to show positive results in a well-planned project and, b) the engineering component is the easiest part of a project: the most difficult is ensuring the farmers' successful participation in a sound, sustainable production, and marketing scheme. Some key recommendations being proposed include the promotion of irrigated agriculture as a key strategy for regional development, and poverty alleviation in the BSA, followed by complete, and upgraded schemes, before embarking on new public irrigation projects. To this end, the private sector should participate in the development of irrigation in the BSA, supported by a legal and institutional framework, to achieve an expansion of public and private schemes, based on sound market studies, to avoid overproduction.